2018
DOI: 10.3847/1538-4357/aaedbf
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Flat Outer Rotation Curve in a Star-bursting Disk Galaxy at z = 1.6

Abstract: Observations of the baryon to dark matter fraction in galaxies through cosmic time are a fundamental test for galaxy formation models. Recent observational studies have suggested that some disk galaxies at z > 1 host declining rotation curves, in contrast with observations of low redshift disk galaxies where stellar or HI rotation curves flatten at large radii. We present an observational counterexample, a galaxy named DSFG850.95 at z = 1.555 (4.1 Gyr after the big bang) that hosts a flat rotation curve betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 70 publications
6
19
0
Order By: Relevance
“…Also, this research would claim that "the dark matter cores" of the black holes shouldn't grow in mass any further, but they might change their gravitational geometry if more matter drops in the surface of the supermassive black hole and increases the time dilation at the center of it (although, black hole collisions might be an exception). That is also consistent with the observed behaviour of dark matter-we can see different shapes of dark matter halos [12] and relatively young galaxies with plenty of dark matter [13]. However, if we were to observe that dark matter halos are not more compact in very young galaxies on average when compared with old ones, we might also surmise that the hypothesis in this research is incorrect.…”
Section: Conclusion and Thoughtssupporting
confidence: 88%
“…Also, this research would claim that "the dark matter cores" of the black holes shouldn't grow in mass any further, but they might change their gravitational geometry if more matter drops in the surface of the supermassive black hole and increases the time dilation at the center of it (although, black hole collisions might be an exception). That is also consistent with the observed behaviour of dark matter-we can see different shapes of dark matter halos [12] and relatively young galaxies with plenty of dark matter [13]. However, if we were to observe that dark matter halos are not more compact in very young galaxies on average when compared with old ones, we might also surmise that the hypothesis in this research is incorrect.…”
Section: Conclusion and Thoughtssupporting
confidence: 88%
“…Moreover, Tiley et al (2019b) reported more than 50% dark matter fraction within 3.5 R e , which is similar to local star-forming disk galaxies (Persic et al 1996;Martinsson et al 2013;Courteau & Dutton 2015). Finally, another study by Drew et al (2018), analyzed a massive star-bursting galaxy at z = 1.55, showed strong evidence of flat RC between 6 − 14 kpc with 44% DM fraction within the effective radius.…”
Section: Introductionsupporting
confidence: 58%
“…Source 850.95 was an outlier at 5.9 ± 3.3 kpc. It is known to be somewhat abnormally large as also traced by Hα kinematics (Drew et al 2018). Source 850.95 also has the lowest signal-tonoise ratio among our sources.…”
Section: Measuring Dust Sizes and Morphologymentioning
confidence: 64%